2014
DOI: 10.1583/14-4671mr.1
|View full text |Cite
|
Sign up to set email alerts
|

Large False Lumen Area Is a Predictor of Failed False Lumen Volume Reduction After Stent-Graft Repair in Type B Aortic Dissection

Abstract: Failed FL volume reduction after TEVAR was associated with a significantly increased rate of mortality or reintervention during follow-up. A larger preprocedure maximum FL area was a predictor of failed FL volume reduction after TEVAR in type B dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…Several studies have suggested that saccular formation of FLs, number of intimal tears, large entry tears ($10 mm), location of the primary entry tear, and configuration of the FL may influence the aortic growth rate during the follow-up period. [23][24][25] In this study, however, the maximum diameter of the affected aorta was the only independent predictor of AD-related deaths. These findings suggested that increased inflow due to a large entry tear and damaged FL media may result in hemodynamic redistribution and acute dissection propagation.…”
Section: Discussioncontrasting
confidence: 60%
“…Several studies have suggested that saccular formation of FLs, number of intimal tears, large entry tears ($10 mm), location of the primary entry tear, and configuration of the FL may influence the aortic growth rate during the follow-up period. [23][24][25] In this study, however, the maximum diameter of the affected aorta was the only independent predictor of AD-related deaths. These findings suggested that increased inflow due to a large entry tear and damaged FL media may result in hemodynamic redistribution and acute dissection propagation.…”
Section: Discussioncontrasting
confidence: 60%
“…The results of the present study indicated that aortic remodelling following TEVAR is more pronounced in acute versus subacute AD, which is not consistent with the results of the VIRTUE Registry. Aortic remodelling after TEVAR may be associated with the characteristics of the dissection (19,(30)(31)(32). Type B AD patients exhibit substantial changes over the disease course (8) that will cause different aortic remodelling patterns after TEVAR in different phases.…”
Section: Discussionmentioning
confidence: 99%
“…Vessel segmentation was performed either automated (lumen boundaries based on voxels with a similar intensity) using manual manipulation 16,21,25,31 or drawing the boundaries of the TL and FL 29,30 or semiautomated with manual selection of the TL and FL. 26 Diameter measurements were performed either perpendicular to a CLL 16,17,21,26,30 or without a CLL, measuring perpendicular to the aortic axis or largest short-axis diameter. 5,12,18,25,27,29,31 Volume measurements were calculated automatically in all studies, with TL and FL calculated separately and total aortic volume by summation of the 2 volumes.…”
Section: Discussionmentioning
confidence: 99%
“…5,12,18,25,27,29,31 Volume measurements were calculated automatically in all studies, with TL and FL calculated separately and total aortic volume by summation of the 2 volumes. 16,21,25,26,2931 Only a small number of studies described the definition of an entry tear as being clear flow of contrast between the TL and FL on at least 2 different views. 12,17,23 One study used CT to identify the entries 17 while others used TEE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation